PENGEMBANGAN ELECTRONIC BOOK BERBASIS STEM UNTUK MENINGKATKAN LITERASI SAINS MATERI ENERGI DAN PERUBAHANNYA PADA SISWA KELAS IV SEKOLAH DASAR - Rustono; Sumarno; Achmad Buchori (STKIP Subang, 2023)
Advances in science and technology encourage education for students to care about and be responsive to issues that develop in society, to have in-depth knowledge and understanding to be applied in solving problems through scientific literacy. Meanwhile, students' scientific literacy skills are still low. So that the use of technology in teaching materials in the form of science learning e-books with the integration of the STEM approach can be a solution to train students' scientific literacy abilities. The aims of this study were 1) to determine the validity of the results of STEM-based e-book development, 2) to determine the practicality of using STEM-based e-books, 3) to determine the effectiveness of STEM-based e-books in increasing students' reading literacy. The type of research used is development research using the ADDIE design. The subjects in this study were 30 students of grade IV SDN Lebo 01. Data collection methods used in this study are interviews, questionnaires, and tests. The data analysis used was quantitative descriptive analysis through requirements testing and hypothesis testing using the Paired Sample T-Test. The results showed that the STEM-based science learning e-book was declared valid by media experts with very good criteria (94%) and subject matter experts with very good criteria (86%). The practicality of the STEM-based science learning e-book was obtained from the average teacher response score of 42 in the very high category and the average score of student responses was 42.8 in the very high category. The results of the effectiveness test showed an average pretest score of 67.83 < an average posttest result of 86.27 and it can be said that STEM-based e-books in science learning are effective in increasing students' scientific literacy.